COMPARING ISLAMIC MODELS OF SUBSTITUTE HEIRS: KHI, HAZAIRIN, SHAHRUR, AND SHIA PERSPECTIVES - Abdul Haris; Syabbul Bachri (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
Although the concept of substitute heirs in the Compilation of Islamic Law (KHI) adopts the inheritance principles of Hazairin's thought, there are notable differences between the two. On the other hand, there is an assumption that the substitute heir system is a new legal framework that has never existed before. However, upon further examination, there are several models of substitute heir systems within the Islamic tradition. This study aims to analyze and compare the substitute heir models conceptualized by the KHI, Hazairin, Shahrur, and Shia schools of thought. This research is a library study employing a qualitative approach with a descriptive-comparative analysis method. The findings reveal that while all models recognize substitute heirs as a vital mechanism to ensure justice in inheritance distribution, significant differences exist in their principles, legal foundations, and heir hierarchies. The KHI limits the portion of substitute heirs so as not to exceed the portion of heirs of the same degree, whereas Hazairin provides full rights without proportional restrictions. Shahrur offers a progressive concept (tardliyah), emphasizing the equalization of grandchildren with children and flexible distribution based on his hudud theory. In contrast, the Shia school employs an exclusive hierarchical system that prioritizes closer relatives and applies the per stirpes distribution method. This study highlights the unique contributions of each model to the discourse on Islamic inheritance law reform and provides insights to address the evolving needs of families and society.